Muslim Filipino Community Legal Handbook Relevant materials on legal and human rights for Muslim communities in the Philippines. - The National Commission on Muslim Fililpinos Bureau of Legal Affairs ([Quezon City, Philippines] [Author], 2016)
This handbook is a guide for Muslim Filipinos to help safeguard their human rights and gain access to legal remedies provided by the government justice system in the Philippines.

This handbook will be extremely beneficial for poor, underserved Muslim Filipino communities that are prone to human rights violations and cases of illegal arrests and mistaken identities.

With this handbook, the NCMF will be providing access to justice to Muslim Filipinos by enhancing their awareness on the basic human and legal right afforded to them by the Philippine Constitution. And in doing so, giving local stakeholders an opportunity to immediately respond to injustice in their communities and gain access to the civil and ciminal justice system.
Chapter 1. The National Commission on Muslim Filipinos -- Chapter 2. Islam, Muslims and Human Rights -- Chatper 3. Relevant Laws and Legal Procedures affecting Muslim Communities -- Chapter 4. Legal Assistance and Other Availabfle Remedies -- Chapter 5. Basic Paralegal Skills -- Annexes.
Keywords: Muslims -- Legal status, laws, etc. -- Philippines; Religious minorities -- Legal status, laws, etc. -- Philippines; Muslims -- Philippines -- Civil rights